Yesus Memberi Makan Lima Ribu Orang: Kajian Model Pembelajaran Berbasis Masalah - Warwer, Fredrik (DIDASKO: Jurnal Teologi dan Pendidikan Kristen, 2023)
The "problem-based learning model" is learning that uses problems as the core of learning, identifies relevant facts and analyzes problems. The Lord Jesus in His teaching also used problems in preaching the gospel, as in "Jesus fed the five thousand". This research aims to create a problem-based modeling of the biblical text Matthew 14:13-21 about “Jesus feeding five thousand people,” with research questions including: 1) what was Jesus' role as an instructor?; 2) what is the role of students as facilitators; and 3) what is the problem-based learning model in the context of “Jesus Feeding the Five Thousand?” This research uses a qualitative approach with phenomenological methods. In problem-based learning modeling, the selection of problems to be discussed is very important. Learning from Jesus who acted as an instructor and told His disciples to feed five thousand people, as an instructor Jesus set an example and example in solving and solving problems. The disciples acted as facilitators and ministered to the five thousand people present at the time. This research can contribute to profiding an alternative study model in understanding the text of the Bible.